Cardiovascular Development Abnormalities in Young Athletes - Adiba Usmankhodjaeva1, Fotima Rakhmatova2, T.A. Taraleva3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The article discusses the issues of small anomalies of heart development in young athletes. The question ofthe admission of young athletes with small anomalies of heart to sports and their impact on the state of thecardiovascular system during exercise is still an open question. To avoid subjectivity and the subsequent overdiagnosis of small anomalies of heart, their objectification is necessary, through a quantitative assessment.